Tin telluride material and preparation method thereof, electrode material and battery
The tin telluride material was prepared by electrochemical anodizing method on the surface of sodium ion battery electrodes, which solved the problems of low efficiency and decay of electrochemical performance of existing sodium ion battery negative electrode materials, and achieved efficient and low-cost electrochemical performance improvement.
Patent Information
- Application Number
- CN202411967904.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
The existing sodium ion battery negative electrode materials have problems such as low efficiency for the first time, excessive working voltage and decay of electrochemical performance, and the preparation process is complicated, which increases production costs.
The tin telluride material is prepared by electrochemical anodizing method on the surface of the tin-containing anode by growing in situ on the surface of the tin-containing anode. The oxidized tellurium in the electrolyte reacts with tin to form SnTe and/or SnTe2 to form a heterojunction material of tin oxide and tin telluride.
The preparation of tin telluride material with simple operation and low cost is realized, avoiding the use of additional processes and conductive agents, and improving electrochemical performance and cycle stability.
Smart Images

Figure CN119800466A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a tin telluride material and a preparation method thereof, an electrode material and a battery. Background Art
[0002] Rechargeable lithium-ion batteries are widely used in electronic devices, electric vehicles and stationary energy storage systems around the world. However, the limited resources and high cost of lithium make it difficult to meet the growing demand. Sodium-ion batteries have a similar working principle to lithium-ion batteries, and sodium resources are abundant and the cost of raw materials is low. Therefore, they are expected to become a complement or substitute for lithium-ion batteries. At present, the development of negative electrode materials for sodium-ion batteries is relatively lagging. The active negative electrode materials of sodium-ion batteries mainly include hard carbon, metal oxides, metal sulfides and metal selenides. The current commercial negative electrode material is hard carbon material, which is mainly derived from the thermal cracking of organic matter, and its nominal specific capacity is 150-200mAh·g -1 , but there are problems of low first efficiency and too high working voltage; metal oxides and metal sulfides usually have high theoretical capacitance, but their low conductivity limits their application as ideal sodium ion battery negative electrode materials; in contrast, tin telluride (SnTe) has high theoretical specific capacity (626mAh / g) and abundant resources. At the same time, the interlayer spacing of metal tin telluride is large and the interlayer van der Waals force is weak, which makes it more conducive to the migration of sodium ions, making it stand out from many metal tellurides and is expected to become the most powerful competitor among many sodium ion battery negative electrode materials. In addition, SnTe is also a semiconductor with a band gap of 0.18eV, which is narrower than SnSe (0.9eV) and SnS (1.01eV), indicating that it has higher conductivity and is more conducive to achieving high rate performance. However, during the cycle of sodium ion batteries, SnTe will undergo severe volume changes and poor conductivity, which will eventually lead to the decline of the electrochemical performance of the material. In response to the above problems, researchers have taken a series of measures, such as nano-structuring SnTe electrode materials and compounding them with carbon nanofibers, amorphous carbon, reduced graphene oxide, heterostructures and other materials. However, due to the low capacity of the carbon material itself, the composite electrode material is not conducive to exerting the high specific capacity characteristics of SnTe electrode materials. The heterojunction can play a good synergistic effect, maintain a high active surface area, provide more disorder / defects for sodium storage, and increase the sodium storage capacity. Therefore, the active electrode composite material can not only improve the conductivity, but also inhibit the agglomeration of active particles and volume effects, thereby effectively improving the electrochemical performance.
[0003] With the in-depth study of SnTe materials by researchers, its preparation method is increasingly diversified, and the controllability of material growth is getting better and better. At present, the commonly used preparation methods mainly include direct alloying method, melt annealing method, liquid phase synthesis method, molecular beam epitaxy method, physical vapor deposition method, chemical vapor deposition method, etc. CN114014278A adopts a melt sintering method, using Sn powder and Te powder as raw materials, mixing and pressing into a blank, carrying out combustion synthesis reaction in a supergravity field, and obtaining SnTe material after cooling. CN114934257A uses a single SnTe target and a radio frequency magnetron sputtering method, adopts a lower target power, does not need to increase the substrate temperature, and does not need to be post-annealed to obtain a crystallized, stoichiometric p-type binary compound SnTe nanofilm material. CN114899379A prepares a high-performance tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material by electrostatic spinning and high temperature calcination process, the material has a tightly woven three-dimensional mesh structure, and is modified with SnSe / SnTe nanoparticles in the porous carbon nanofiber. The resulting composite material exhibits excellent sodium ion storage capacity, rate performance and cycle stability. CN116014090A prepares a double carbon-coated SnTe / CoTe2 composite material by combining electrostatic spinning technology and heat treatment process, the composite material has a core-shell structure with a hollow porous SnTe / CoTe2 as the core, an outer layer coated with carbon nanofiber carbon fiber, and the internal gap of the carbon nanofiber is filled with carbon material. The composite material exhibits excellent rate performance, high reversible specific capacity and long cycle life when used as a negative electrode material for sodium ion batteries. CN116804269A provides a method for growing SnTe nanowire arrays on substrates by CVD method, using SnTe template as growth substrate, coating gold particles on SnTe template; placing SnTe powder in high temperature zone, SnTe template in low temperature zone, heating SnTe powder in high temperature zone to sublimate into gaseous state, diffuse to low temperature zone and grow into SnTe nanowire film array under the induction of gold particles. CN115963154A adopts hydrothermal method to compound SnTe and SnO2 to form heterojunction, and it is found that the gas sensitive performance of the synthesized heterojunction gas sensor is greatly improved. CN105819411A discloses a hydrothermal method for synthesizing and preparing octahedral SnTe nanocrystals, and the specific steps are firstly mixing Te powder and NaOH to obtain a mixed solution by hydrothermal reaction, then adding SnCl2 and NaBH4, and obtaining octahedral SnTe pure phase material after secondary hydrothermal reaction. CN107814571A Ge, Sn and Te powder raw materials mixed in a certain molar ratio are placed in a closed container, anhydrous ethanol is injected and deoxidation and / or protection treatment is performed, ball milling is performed, and pressure sintering is performed to obtain a dense SnTe nanocomposite material.CN110061219A discloses a method for preparing self-supporting SnTe / C nanofibers by electrospinning. The obtained SnTe / C is a uniform nanofiber with a diameter of about 100 to 300 nm and excellent electrochemical properties.
[0004] In summary, the current preparation process of SnTe or SnTe / SnO2 composite materials has the disadvantages of long reaction time, complex preparation process, toxic pollutants generated during the synthesis process, etc., and the prepared materials are often in powder form. If they are to be used as electrode materials, additional processes are required to mix the powder with a conductive agent and a binder to prepare the electrode material. The additional preparation process and the use of conductive agents and binders not only increase the production cost, but also reduce the specific volume energy density and specific mass energy density of the electrode material. Therefore, it is very necessary to study and explore a simple operation, low cost, stable structure, easy to promote efficient synthesis of SnTe or SnTe / SnO2 electrode materials. Summary of the invention
[0005] The purpose of this application is to provide a tin telluride material and a preparation method thereof, an electrode material and a battery.
[0006] This application adopts the following technical solutions:
[0007] The first aspect of the present application discloses a method for preparing a tin telluride material, comprising:
[0008] The anode and the cathode are placed in an electrolyte, and voltage is applied to the anode and the cathode to react to obtain the tin telluride material; wherein the anode contains tin, and the electrolyte includes oxidized tellurium, an organic solvent with a volume ratio of 90% to 99.5% and water with a volume ratio of 0.5% to 10%.
[0009] It should be noted that the preparation method of the present application uses an electrochemical anodization method to generate Sn on the surface of the anode containing metallic tin under the action of an electric field force. 2+ and / or Sn 4+ , the oxidized tellurium in the electrolyte will be enriched near the anode and reduced to Te 2- , thereby reacting to form SnTe and / or SnTe2; in addition, a small amount of water in the electrolyte will produce OH - , OH - Also with Sn 2+ and / or Sn 4+ The reaction generates SnO and / or SnO2. In the electrolyte of the present application, the organic solvent is used as a non-aqueous medium to provide a liquid medium environment for the electrolyte; a small amount of water can dissolve the tellurium source to generate free oxidized tellurium. It should be noted that too much water will cause Sn 2+ / Sn 4+ Priority and OH in water- The SnTe or SnTe2 is difficult to generate by reacting to generate oxides. Through the preparation method of the present application, tin oxide and tin telluride can be prepared by in-situ growth on the surface of the tin-containing anode. The obtained electrode with tin oxide and tin telluride can be directly used as the electrode material of the sodium ion battery without the need for an additional process to deposit the tin telluride material on the electrode surface to obtain the electrode material.
[0010] It should also be noted that in the present application, according to actual needs, metal tin can be replaced by other metals (for example, iron, zinc, cobalt, nickel, etc.), and / or tellurium can be replaced by other elements (for example, selenium, sulfur, etc.).
[0011] In one implementation of the present application, the electrolyte further includes a conductivity enhancer. It should be noted that the conductivity enhancer can form free ions when dissolved in water, which can increase the conductivity of the electrolyte and accelerate the reaction.
[0012] In one implementation of the present application, the tellurium in the oxidation state comprises TeO4 2- 、TeO3 2- 、HTeO4 - 、HTeO3 - At least one of .
[0013] In one implementation of the present application, in the electrolyte, the concentration of the oxidized tellurium is 0.01M to 0.2M.
[0014] In one implementation of the present application, the concentration of the oxidized tellurium is 0.02M.
[0015] In one implementation of the present application, the organic solvent includes at least one of carbonate substances, alcohol substances, ketone substances, ether substances and ester substances.
[0016] In one implementation of the present application, the alcohol substance includes at least one of ethylene glycol, glycerol, diethylene glycol and polyethylene glycol.
[0017] In one implementation of the present application, the organic solvent is glycerol.
[0018] In one implementation of the present application, the electrolyte further includes a conductivity enhancer.
[0019] In one implementation of the present application, the concentration of the conductivity enhancer is 0.01M to 0.2M.
[0020] In one implementation of the present application, the conductivity enhancer includes at least one of an inorganic salt, an acid, and a base.
[0021] In one implementation of the present application, the conductivity enhancer includes inorganic fluoride. It should be noted that fluoride ions can effectively improve the conductivity of the electrolyte and have stronger corrosiveness.
[0022] In one implementation of the present application, the inorganic fluoride includes at least one of NaF, KF and NH4F.
[0023] In one implementation of the present application, the conductivity enhancer is NH4F.
[0024] In one implementation of the present application, the electrolyte includes 0.02M sodium tellurite, 95% by volume of the organic solvent, 5% by volume of water, and 0.1M NH4F.
[0025] In one implementation of the present application, the tin telluride material includes a tin oxide tin telluride heterojunction material. It should be noted that according to the preparation method of the present application, a tin oxide / tin telluride heterojunction material can be obtained. Tin oxide / tin telluride heterojunction material (SnOx / SnTey (x, y=1, 2)) refers to a composite heterojunction interface formed by tin oxide and telluride. A heterojunction refers to an interface formed by two different semiconductor materials, which may have different band structures, bandgap widths, and carrier concentrations; the formation of a heterojunction usually causes changes in the band structure at the interface, thereby affecting the behavior of electrons and holes.
[0026] In one implementation of the present application, the tin oxide telluride heterojunction material includes at least one of a composite of tin telluride (SnTe2, SnTe) and tin oxide (SnO2, SnO). It should be noted that in the preparation method of the present application, since the electrolyte contains water, the OH present in the reaction process - It will participate in the competitive reaction to produce SnO or SnO2, so the conditions for obtaining SnTe or SnTe2 are relatively harsh. The tin-based compound prepared in the present application can be a complex composed of any one or two of SnTe2 and SnTe and any one or two of SnO2 and SnO, for example, it can be a SnTe2 / SnO2 complex, SnTe / SnTe2 / SnO2 complex, SnTe / SnTe2 / SnO / SnO2 complex, etc.
[0027] In one implementation of the present application, the voltage is 60V to 200V.
[0028] In one implementation of the present application, the voltage is 140V.
[0029] In one implementation of the present application, the reaction time is 10 minutes to 120 minutes.
[0030] In one implementation of the present application, the reaction time is 10 minutes to 30 minutes.
[0031] In one implementation of the present application, the reaction temperature is 20°C to 30°C.
[0032] In one implementation of the present application, the reaction temperature is room temperature.
[0033] In one implementation of the present application, after the reaction is completed, the process further includes: removing the anode and washing it with deionized water and / or alcohol.
[0034] The second aspect of the present application discloses an electrode material prepared by the preparation method disclosed in the first aspect of the present application. It should be noted that, through the preparation method of the present application, a tin telluride material can be prepared by in-situ growth on the surface of a tin-containing anode, and the electrode with the tin telluride material can be directly used as an electrode material and applied to sodium ion batteries, etc., without the need for an additional process to deposit the tin telluride material on the electrode material.
[0035] The third aspect of the present application discloses a battery, which includes the electrode material disclosed in the second aspect of the present application.
[0036] In one implementation of the present application, the battery is a sodium ion battery.
[0037] The beneficial effects of this application are:
[0038] The preparation method of the present application prepares tin telluride material by electrochemical anodization, which is simple, convenient and low-cost to operate, and the tin telluride material is grown in situ on the electrode, without the need for additional steps to deposit the tin telluride material on the electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a surface SEM morphology image of the reaction product sample involved in this application.
[0040] Figure 2 It is an element distribution map corresponding to the surface morphology of the reaction product sample involved in this application.
[0041] Figure 3 is the XRD diagram of the reaction product sample involved in this application.
[0042] Figure 4 It is a charge and discharge curve diagram of the SnTe / SnO2 electrode material sodium ion battery involved in this application.
[0043] Figure 5 This is a graph showing the cycle stability test results of the SnTe / SnO2 electrode material sodium ion battery involved in this application.
[0044] Figure 6This is a graph showing the rate performance test results of the SnTe / SnO2 electrode material sodium ion battery involved in this application. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below by specific embodiments in conjunction with the accompanying drawings. In the following embodiments, many detailed descriptions are intended to enable the present application to be better understood. However, those skilled in the art can effortlessly recognize that some of the features can be omitted in different situations, or can be replaced by other materials and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations according to the description in the specification and the general technical knowledge in the art.
[0046] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and are not meant to be a required sequence, unless otherwise specified that a certain sequence must be followed.
[0047] The serial numbers assigned to the components in this article, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning.
[0048] The present application relates to a method for preparing a tin telluride material, a method for preparing an electrode material containing the tin telluride material (also referred to as a tin oxide / tin telluride composite film electrode material), an electrode material and a battery.
[0049] In a specific embodiment, the preparation method of the tin telluride material of the present application includes: placing an anode and a cathode in an electrolyte, and applying voltage to the anode and the cathode for reaction to obtain a tin telluride material or an electrode material containing the tin telluride material, wherein the anode contains tin and the electrolyte contains oxidized tellurium.
[0050] In a specific embodiment, the anode includes tin or a tin alloy. Thus, a tin source can be provided for the reaction, and in the redox reaction, the metal tin of the anode generates Sn. 2+ and / or Sn 4+ , which can react with tellurium enriched near the tin-containing electrode, and then grow tin telluride in situ on the surface of the tin electrode.
[0051] In one embodiment, the surface of the anode contains tin or a tin alloy.
[0052] In a specific embodiment, the anode is tin or a tin alloy, such as a copper-tin alloy.
[0053] In a specific embodiment, the cathode may be graphite, carbon nanotubes, carbon fibers or platinum (Pt).
[0054] In one embodiment, the tellurium in the oxidation state comprises TeO4 2- 、TeO3 2- 、HTeO4 - 、HTeO3 - It should be noted that under the action of the electric field, TeO4 2- 、TeO3 2- 、HTeO4 - 、HTeO3 - It will be enriched near the anode and reduced to Te 2- , thereby reacting to form SnTe (tin telluride) and / or SnTe2 (tin ditelluride), and growing tin telluride in situ on the anode surface.
[0055] In a specific embodiment, the electrolyte contains 0.01 M to 0.2 M of the tellurium source. For example, the electrolyte may contain 0.01 M, 0.05 M, 0.1 M, 0.15 M or 0.2 M of the tellurium source.
[0056] In one embodiment, the electrolyte contains an organic solvent.
[0057] In a specific embodiment, the electrolyte contains 90% to 99.5% by volume of an organic solvent. For example, the electrolyte may contain 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5% by volume of an organic solvent. It should be noted that since there cannot be too much water in the electrolyte, an organic solvent is used as a non-aqueous medium to provide a liquid environment for the electrolyte.
[0058] In a specific embodiment, the organic solvent includes at least one of carbonate substances, alcohol substances, ketone substances, ether substances and ester substances.
[0059] In a specific embodiment, the alcohol substance includes at least one of ethylene glycol, glycerol, diethylene glycol and polyethylene glycol. Preferably, the organic solvent is glycerol.
[0060] In a specific embodiment, the electrolyte contains a conductivity enhancer. It should be noted that the conductivity enhancer can increase the conductivity of the electrolyte and accelerate the reaction.
[0061] In a specific embodiment, the electrolyte contains 0.01 M to 0.2 M of the conductivity enhancer. For example, the electrolyte may contain 0.01 M, 0.05 M, 0.1 M, 0.15 M or 0.2 M of the conductivity enhancer.
[0062] In a specific embodiment, the conductivity enhancer includes at least one of an inorganic salt, an acid, and a base.
[0063] In a specific embodiment, the conductivity enhancer is an inorganic fluoride. It should be noted that fluoride ions can effectively increase the conductivity of the electrolyte and have stronger corrosiveness.
[0064] In a specific embodiment, the inorganic fluoride includes at least one of NaF, KF and NH4F. Preferably, the conductivity enhancer is NH4F.
[0065] In a specific embodiment, the electrolyte contains a small amount of water. It should be noted that water can be used to dissolve the tellurium source and the conductivity enhancer to generate free oxidized tellurium. Since the electrolyte contains water, OH - , will react with Sn generated at the anode 2+ / Sn 4+ The reaction generates SnO / SnO2. It should also be noted that too much water will cause Sn 2+ / Sn 4+ Priority and OH in water - React to form oxides, which makes it difficult to form SnTe or SnTe2.
[0066] In a specific embodiment, the electrolyte contains 0.5% to 10% water by volume. For example, the electrolyte may contain 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% water by volume.
[0067] In one specific embodiment, the water contained in the electrolyte is deionized water.
[0068] In one embodiment, the voltage applied during the reaction is 60 V to 200 V. For example, the voltage may be 60 V, 80 V, 100 V, 120 V, 140 V, 160 V, 180 V, or 200 V.
[0069] In a specific embodiment, the voltage is applied by a DC regulated power supply.
[0070] In a specific embodiment, the reaction time is 10 minutes to 120 minutes. For example, the reaction time can be 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes or 120 minutes.
[0071] In a specific embodiment, the reaction temperature is 20° C. to 30° C. For example, the reaction temperature may be 20° C., 21° C., 22° C., 23° C., 24° C., 25° C., 26° C., 27° C., 28° C., 29° C. or 30° C. It should be noted that the preparation method of the present application can be carried out at room temperature.
[0072] In a specific embodiment, after the reaction is completed, the anode is taken out and cleaned with deionized water and / or alcohol.
[0073] In a specific embodiment, the tin-based compound prepared in the present application is grown in situ on the surface of the electrode, so that the electrode can be directly used as an electrode material in sodium ion batteries and the like.
[0074] In a specific embodiment, the tin oxide / tin telluride heterojunction material prepared in the present application includes at least one of SnTe2, SnTe, SnO2, SnO or a composite thereof. It should be noted that in the preparation method of the present application, since the electrolyte contains water, the OH present in the reaction process - It will participate in the competitive reaction to produce SnO or SnO2, so the conditions for obtaining SnTe or SnTe2 are relatively harsh. The tin-based compound prepared in the present application can be a complex composed of any one or two of SnTe2 and SnTe and any one or two of SnO2 and SnO, for example, it can be a SnTe2 / SnO2 complex, SnTe / SnTe2 / SnO2 complex, SnTe / SnTe2 / SnO / SnO2 complex, etc.
[0075] In a specific embodiment, the electrolyte includes 0.02M sodium telluride, 5% water by volume, 0.1M NH4F and the remaining volume of glycerol. The voltage is 80V, the reaction time is 10 minutes, the reaction temperature is 25°C, and the obtained product is SnO2 / SnTe2 heterojunction material.
[0076] The present application is further described in detail below by specific examples. The following examples are only further described for the present application and should not be construed as limiting the present application. In the present example, unless otherwise specified, the reagents and instruments used are all commercially available, and the experimental operations are carried out in accordance with the product instructions and conventional experimental specifications.
[0077] Example:
[0078] (1) Cut the copper / Sn foil into 1×2 cm 2 Size, then clean with alcohol and deionized water respectively and dry for later use;
[0079] (2) Anodic oxidation of metal is carried out in a double-electrode electrolytic cell, with copper foil as the anode and Pt (platinum) as the cathode, and the electrolyte is a mixed solution of 0.02M sodium tellurate + 0.1M ammonium fluoride + glycerol (Gly ≥ 99.8wt.%) + 5% water by volume;
[0080] (3) A 140V voltage is applied to the electrolytic cell electrodes through a DC regulated power supply, and the reaction time is controlled to be 30 minutes at room temperature (25°C). After the reaction is completed, the sample (anode) is taken out and the sample surface is cleaned with deionized water and alcohol in turn, and dried for subsequent characterization.
[0081] The characterization results are as follows Figures 1 to 3 As shown, Figure 1 is a surface SEM (scanning electron microscope) morphology of the reaction product sample involved in this application, Figure 1 It can be seen that the surface of the sample presents a porous nanostructure. Figure 2 is the element distribution map of the reaction product sample surface involved in this application, Figure 2 It can be seen that Sn, Te and O elements are evenly distributed on the sample surface. The phase structure of the reaction product can be determined by XRD (X-ray diffraction) observation. The sample was scraped from the anode surface and treated at 2000℃ in Ar atmosphere for 4h, and XRD observation was performed. Figure 3 is the XRD diagram of the reaction product sample involved in this application, Figure 3 It can be seen that the positions of the diffraction peaks correspond to SnTe (PDF#65-0308) and SnO2 (PDF#29-1484), respectively.
[0082] Half-cell test was conducted, using Cu grown with SnTe / SnO2 material as positive electrode, metal Na sheet as negative electrode, glass fiber as separator, and 1M NaPF6 dissolved in acrylate + 2% fluoroethylene carbonate as electrolyte, assembled into button cell, and electrochemical sodium storage performance test was conducted, including charge and discharge test, cycle performance test, and rate performance test. The charge and discharge test voltage range of the battery was 0.005-2.0V (vs. Na / Na+), and the charge and discharge current was 100mA / g. The charge and discharge curves and cycle performance results of the electrode material are shown in the figure. Figure 4 and Figure 5 As shown, Figure 4 is a charge and discharge curve diagram of the SnTe / SnO2 electrode material sodium ion battery involved in this application, Figure 5 This is a graph of the cycle stability test results of the SnTe / SnO2 electrode material sodium ion battery involved in the present application. The results show that the electrode material still retains a specific capacity of about 400mAh / g after 100 cycles of testing. Figure 6This is a graph of the rate performance test results of the SnTe / SnO2 electrode material sodium ion battery involved in the present application. The rate performance of the electrode material shows that the electrode material still has good recovery ability after high-rate charge and discharge.
[0083] In summary, by characterizing the samples prepared in this embodiment, it can be known that the reaction product is SnTe / SnO2 material. That is, according to this embodiment, a tin oxide / tin telluride heterojunction material can be generated on the electrode surface. The electrode having the tin oxide / tin telluride heterojunction material is used as an electrode material for a sodium ion battery, which has good cycle stability and rate performance.
[0084] The above contents are further detailed descriptions of the present application in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present application is limited to these descriptions. For ordinary technicians in the technical field to which the present application belongs, several simple deductions or substitutions can be made without departing from the concept of the present application.
Claims
1. A method for preparing a tin telluride material, characterized in that: include: placing an anode and a cathode in an electrolyte, and applying voltage to the anode and the cathode to react, thereby obtaining the tin telluride material; The anode contains tin, and the electrolyte includes oxidized tellurium, 90% to 99.5% by volume of an organic solvent, and 0.5% to 10% by volume of water.
2. The preparation method according to claim 1, characterized in that: The tellurium oxidation state includes TeO4 2- 、TeO3 2- 、HTeO4 - 、HTeO3 - At least one of; Preferably, in the electrolyte, the concentration of the oxidized tellurium is 0.01M to 0.2M; Preferably, in the electrolyte, the concentration of the oxidized tellurium is 0.02M.
3. The preparation method according to claim 1 or 2, characterized in that: The organic solvent includes at least one of carbonate substances, alcohol substances, ketone substances, ether substances and ester substances; Preferably, the alcohol substance includes at least one of ethylene glycol, glycerol, diethylene glycol and polyethylene glycol; Preferably, the organic solvent is glycerol.
4. The preparation method according to claim 3, characterized in that: The electrolyte also includes a conductivity enhancer; Preferably, in the electrolyte, the concentration of the conductivity enhancer is 0.01M to 0.2M; Preferably, the conductivity enhancer comprises at least one of an inorganic salt, an acid and a base; Preferably, the conductivity enhancer comprises an inorganic fluoride; Preferably, the inorganic fluoride comprises at least one of NaF, KF and NH4F; Preferably, the conductivity enhancer is NH4F.
5. The preparation method according to claim 4, characterized in that: The electrolyte includes 0.02M sodium tellurite, 95% by volume of the organic solvent, 5% by volume of water and 0.1M NH4F.
6. The preparation method according to claim 1, characterized in that: The tin telluride material includes a tin oxide tin telluride heterojunction material.
7. The preparation method according to claim 1, characterized in that: The voltage is 60V to 200V; Preferably, the voltage is 140V; Preferably, the reaction time is 10 to 120 minutes; Preferably, the reaction time is 10 to 30 minutes; Preferably, the reaction temperature is 20°C to 30°C; Preferably, the reaction temperature is room temperature; Preferably, after the reaction is finished, the method further comprises: taking out the anode and washing it with deionized water and / or alcohol.
8. An electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. A battery, characterized in that: The battery comprises the electrode material according to claim 8.
10. The battery according to claim 9, characterized in that The battery is a sodium ion battery.
Citation Information
Patent Citations
Preparation method of octahedral SnTe nanocrystals with triangle as basic unit
CN105819411A
SnTe nano composite material and preparation method and application thereof
CN107814571A
Electrostatic spinning preparation method of self-supporting SnTe / C nanofiber
CN110061219A
Method for preparing SnTe thermoelectric material
CN114014278A
High-performance tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material and preparation method thereof
CN114899379A